Experiences of college students with physical impairment during online classes in physical education - Joseph Lobo; Jan Carhley Cruz; Jayvey Cruz; Jerizza Abella; Wilrenz Castro; Michael Louie Celis; Bryan Dale Bernardo (UIR Press, 2022)
Due to the rampant spread of COVID-19, schools have shut down worldwide, resulting in dramatic changes in education. Physically impaired students are one of the groups that were highly affected due to these drastic changes. On a positive note, according to previously conducted studies, online physical education can provide students with disabilities a context in which self-efficacy and participation are promoted, which may lead to improved academic achievement. In this, the qualitative-exploratory study is focused on unraveling the experiences and challenges of students with physical impairment during online PE classes amidst the pandemic. Ten (10) samples of college students within Pampanga, Philippines, participated in the study. This study has analyzed in-depth college students' concepts, thoughts, and experiences during their online PE. Narratives from the participants were analyzed using Manual Qualitative Analysis through transcriptions, coding, categorization, and thematic analyses. Based on the findings, three central themes have emerged: (a) better, fitter, healthier, and happier, (b) overcoming challenges; and (c) a healthy mind in a healthy body. Indeed, there is a need to ameliorate the delivery of acclimated or special needs physical education by making teachers more involved and dynamic in their tasks and lessons. PE teachers supervising students with physical impairment should determine their capacities and measures that need enforcement to support participation in sports and fitness. Aside from the findings discovered, an in-depth analysis of how academic performance, personality types, parental support, or sports participation can affect students' perception or experience in online Physical education classes is highly suggested.